Assimetria de informação: categorias de informações que fundamentam os questionamentos nas conference calls de resultados - Saraiva, Mayane Tiara da Rocha Maia (Universidade do Vale do Rio dos Sinos, 2021)
The issue of information asymmetry, established in the corporate context of the Brazilian capital market, occurs mainly due to the separation of ownership and control (majority and minority) and verified in studies reviewed and recognized by regulatory bodies, which institute the periodic disclosure of statements accounting. Management uses earnings conference calls to explain and comment on the information made available to the market. Considering the above, this dissertation aimed to verify the main categories of information that represent the concerns of the Brazilian capital market, expressed through the questions made in the result conference calls. For this, the content of the transcript of 76 conference calls for the year 2019, coming from 19 firms belonging to various market sectors, was analyzed. From this analysis, it was possible to infer that the information category that most worries the capital market is the operational one, followed by the investment category. Which led to the conclusion that 34% of the questions analyzed confirm the asymmetry of information and the importance of conference calls as a communication channel to mitigate it. The research also contributed with literature as it explained the information categories of questions by corporate structure, noting that the market's concerns are concentrated in firms with defined corporate control, thus ratifying previous studies that point out the malfunctioning of the market of Brazilian capitals, given their characteristics linked to the corporate, economic, financial, and legal structure. As a limitation of the study, thematic agglutination in the same questioning is presented, possibly because of the questioner seeking to optimize the limited number of questions. As for suggestions for future research, the study of some aspects to be explored is presented, such as: the behavioral biases of management representatives: the executive's posture refers to commitment to the fairness of the market or the executive's posture is more of concealment and the behavioral biases of management representatives under analysis prior to the disclosure of the fraud.
Keywords: Conference call de resultado; Mercado de Capitais Brasileiro; Assimetria de informação; Categorias de informações; Estrutura Societária Brasileira; Conference calls earnings; Brazilian capital market; Information asymmetry; Information categories; Brazilian corporate structure; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis